Uso do sistema de modelagem na enseada do Pontal de Coruripe, Alagoas - Azevedo Neto, João Lessa de (2015)
This Reserch área is located at the Pontal de Coruripe in the cove of the same name, which is located in the Coruripe city, Alagoas south coast, at a distance from the Maceió capital, about 90 Km. The methodology used was based on the computational tool Coastal Modeling System - SMCBrasil which features interface Brazilian Coastal Modeling System (SMC-Brazil) and SMC-TOOLS including database (IH-Data): bathymetries the coast (BACO) and wave data (DOW), meteorological tide (GOS) and astronomical tide (GOT); characterization tool of Environmental Variables (AMEVA); Flood Dimension tool (DCRZ); maritime climate reconstruction tool on the coast and calculation of sediment transport, tai as Morphodynamic Program beaches (MOPLA); Cross Profile program the beaches (PETRA); Module beaches in balance and Terrain Modeling (MMT). Other software that complement the SMC are the SURF and MATLAB. The SURFER has functions that allow: Data entry through the sheet to the bathymetry of detail; different file import SURFER (* .slk); create 3D maps from data bathymetry xyz; viewing figures of the generated maps; Generation maps and mesh points of the maps. The present MATLAB functions: Construction Figures and build functions; Formulations of calculation functions and symbolic variables; Figures generated presented the Hypercube methodology. The results presented in the repor of the pre-process, was used the historical basis of data reanalysis of 60 years, from the data interpolation detail bathymetry, with high resolution and the union of the meshs, generating a atual mash in that the points of deep water with shallow water interact, o espalhamento direcional, a refração e difração induzida onda onda, e o atrito com o fundo.Was generated maps which defined two distinct sectors, both sheltered beach: A stretch of beach to the south, near Rio Coruripe, beach with low occupancy, the currents occur from south to north, with magnitude between 0.05m / to 0.08 m / s and wave height that reaches 50cm. The other stretch of beach north near the sandy tip, with consolidated occupation, the northern currents south of magnitude between 0.02 m / s 0,09m / s and wave height below 50 cm. The current are in a central sector between the two passages, leading the flow to deeper water within the Pontal do Coruripe cove. The use of vulnerability and risk matrix that defines the risk exposure is low, due to the socioeconomic influences analyzed due to the vulnerability of the study area is high, due to the fragility of coastal ecosystems and suffered human pressures on these environments. Therefore, it can be said that the study area, according to vulnerability and risk matrix, falls as low risk.